Placental growth factor in assessment of women with suspected pre-eclampsia to reduce maternal morbidity: a stepped wedge cluster randomised control trial (PARROT Ireland). (13th August 2021) - Hayes-Ryan, D; Khashan, A S; Hemming, K; Easter, C; Devane, D; Murphy, D J; Hunter, A; Cotter, A; McAuliffe, F M; Morrison, J J; Breathnach, F M; Dempsey, E; et al.
Abstract: Objective: To determine whether the addition of placental growth factor (PlGF) measurement to current clinical assessment of women with suspected pre-eclampsia before 37 weeks' gestation would reduce maternal morbidity without increasing neonatal morbidity. Design: Stepped wedge cluster randomised control trial from 29 June 2017 to 26 April 2019. Setting: National multisite trial in seven maternity hospitals throughout the island of Ireland Participants: Women with a singleton pregnancy between 20 +0 to 36 +6 weeks' gestation, with signs or symptoms suggestive of evolving pre-eclampsia. Of the 5718 women screened, 2583 were eligible and 2313 elected to participate. Intervention: Participants were assigned randomly to either usual care or to usual care plus the addition of point-of-care PlGF testing based on the randomisation status of their maternity hospital at the time point of enrolment. Main outcomes measures: Co-primary outcomes of composite maternal morbidity and composite neonatal morbidity. Analysis was on an individual participant level using mixed-effects Poisson regression adjusted for time effects (with robust standard errors) by intention-to-treat. Results: Of the 4000 anticipated recruitment target, 2313 eligible participants (57%) were enrolled, of whom 2219 (96%) were included in the primary analysis. Of these, 1202 (54%) participants were assigned to the usual care group, and 1017 (46%) were assigned the intervention of additional point-of-care PlGF testing. The results demonstrate that the integration of point-of-care PlGF testing resulted in no evidence of a difference in maternal morbidity—457/1202 (38%) of women in the control group versus 330/1017 (32%) of women in the intervention group (adjusted risk ratio (RR) 1.01 (95% CI 0.76 to 1.36), P=0.92)—or in neonatal morbidity—527/1202 (43%) of neonates in the control group versus 484/1017 (47%) in the intervention group (adjusted RR 1.03 (0.89 to 1.21), P=0.67). Conclusions: This was a pragmatic evaluation of an interventional diagnostic test, conducted nationally across multiple sites. These results do not support the incorporation of PlGF testing into routine clinical investigations for women presenting with suspected preterm pre-eclampsia, but nor do they exclude its potential benefit. Trial registration: ClinicalTrials.gov NCT02881073 .